482 Intervention packages for the prevention of unintentional injuries among children. (20th November 2022) - Zia, Nukhba; Ashraf, Lamisa; Agrawal, Priyanka; Green, Abigail; Vincenten, Joanne; MacKay, Morag; Bachani, Abdulgafoor M
Abstract : Background: Unintentional injuries are the leading cause of death among children under 19 years of age globally. Existing literature lacks evidence on effectiveness of unintentional injury prevention intervention packages. We conducted an evidence synthesis exercise to collate data on effectiveness of intervention packages (education, engineering, and enforcement) for unintentional injuries, namely road traffic injuries (RTI), drowning, poisoning, burns and falls. Methods: A stepwise approach to gathering evidence on child injury prevention interventions was undertaken with reviews of (1) systematic reviews published between 2008 and 2020, (2) primary studies published between 2020 and 2021, and (3) hand searched articles. The study population included children under 20 years. Results: RTI prevention intervention packages including education programs and engineering measures like, free car seats distribution increased car seat use by 17.10% and reduced inappropriate use by 49.00%. A combination of interventions including 'legislation, engineering, education, and personal protection' reduced the risk of drowning mortality in Bangladesh (RR= 0.44 (0·20–0·98)). Education and provision of safety equipment increased the likelihood of safe storage of medicines by 2.51 times compared to that of usual safety education or no education. Education and discounted safety equipment, including thermometers, increased use of safe practices like checking hot tap water temperatures. Fall safety education and equipment distribution increased use of stair gates by 26.00% (95% CI 5.00 – 51.00%). Conclusion: Further research is needed to quantify the effectiveness of packaged interventions. Efforts to reduce unintentional injuries should not be siloed as its effects extend beyond the field of injury on to addressing a range of sustainable development goals.